Vaping among Norwegians who smoke or formerly smoked: reasons, patterns of use, and smoking cessation activity - Ingeborg Lund; Gunnar Sæbø (BMC, 2023)
Abstract Background The majority of Norwegians who use e-cigarettes are adults who have smoked. Little is known about vaping reasons and -patterns in this group. The aim of this paper was to study vaping prevalence, patterns, and motivations among adults who smoke. Furthermore, to investigate smoking intensity and smoking cessation behaviour differences between those who vape and those who do not. Methods This study was based on two separate Norwegian samples: People who had ever smoked, from 2017 (N = 2099), and people who currently smoked and recent quitters, from 2018/2019 (N = 1336). Measures of vape frequencies, vape motives, and smoking cessation behaviours were utilised in descriptive analyses of relationships between vaping and smoking behaviour. Results Less than 1 in 10 in the ever-smoked group, 1 in 5 of the currently smoked or recently quit group, were currently vaping. Ever trial rates for vaping were much higher at 1 in 3 in the ever-smoked group, and 1 in 2 in the currently smoked or recently quit group. Dual use with combustible cigarettes was common, but people who smoked tended to use e-cigarettes less frequently while those who formerly smoked tended to use them more frequently. Both quitting attempts and smoking intensity reduction were positively associated with vaping, and the most common reasons for e-cigarette use were reported to be desires to reduce harm, to stop smoking, or to reduce smoking intensity. Conclusion The results indicate that Norwegians who smoke tend to see e-cigarettes as a tool to reduce or completely stop smoking. The predominance of use-motivations related to reducing harm points at the importance of conveying correct information about relative harmfulness of tobacco- and nicotine products.